Susceptibility of primary ovine dorsal soft palate and palatine tonsil cells to FMDV infection - Sarry, Morgan; Laloy, Eve; Relmy, Anthony; Romey, Aurore; Bernelin-Cottet, Cindy; Salomez, Anne-Laure; Huet, Hélène; Hägglund, Sara; Valarcher, Jean-François; Bakkali Kassimi, Labib; Blaise-Boisseau, Sandra (Frontiers in Veterinary Science, 2024)
Foot and mouth disease (FMD) is a highly contagious viral disease affecting cloven-hoofed animals. This disease is one of the most important in animal health due to its significant socio-economic impact, especially in case of an outbreak. One important challenge associated with this disease is the ability of the FMD virus (FMDV) to persist in its hosts through still unresolved underlying mechanisms. The absence of relevant in vitro models is one factor preventing advancement in our understanding of FMDV persistence. While a primary bovine cell model has been established using cells from FMDV primary and persistence site in cattle, it appeared interesting to develop a similar model based on ovine anatomical sites of interest to compare host-pathogen interactions. Thus, epithelial cells derived from the palatine tonsils and the dorsal soft palate were isolated and cultured. Their epithelial nature was confirmed using immunofluorescence. Following monolayer infection with FMDV O/FRA/1/2001 Clone 2.2, the FMDV-sensitivity of these cells was evaluated. Dorsal soft palate (DSP) cells were also expanded in multilayers at the air-liquid interface to mimic a stratified epithelium sensitive to FMDV infection. Our investigation revealed the presence of infectious virus, as well as viral antigens and viral RNA, up to 35 days after infection of the cell multilayers. Further experiment with DSP cells from different individuals needs to be reproduced to confirm the robustness of the new model of persistence in multilayer DSP. The establishment of such primary cells creates new opportunities for FMDV research and analysis in sheep cells.